Get comprehensive solutions to your problems with IDNLearn.com. Join our knowledgeable community to find the answers you need for any topic or issue.
Sagot :
Answer:
Step-by-step explanation:
First switch the y and x values:
[tex]x=3^y[/tex]
Take the natural log of both sides to get:
[tex]\ln(x)=y*\ln(3)[/tex]
Separate the y value:
[tex]y=\frac{\ln(x)}{\ln(3)}[/tex]
The inverse of the exponential function will be:
"y = [tex]\frac{ln(x)}{ln(3)}[/tex]".
Exponential function
According to the question,
The function, y = [tex]3^x[/tex]
By switching "x" and "y" of both sides of the function,
→ x = [tex]3^y[/tex]
Now,
By taking "log" both sides,
ln(x) = y × ln(3)
By separating the terms, we get
y = [tex]\frac{ln(x)}{ln(3)}[/tex]
Thus the above response is correct.
Find out more information about exponential function here:
https://brainly.com/question/2456547
We are happy to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. Find clear answers at IDNLearn.com. Thanks for stopping by, and come back for more reliable solutions.